LAS INSTITUCIONES DE EDUCACIÃ“N SUPERIOR Y SU EVALUACIÃ“N - RodrÃguez, Martha Elena Jaime (European Scientific Journal, ESJ, 2013)
The interest of the undersigned to address the issue presented here arises from the need to know the perception of teachers in terms of three dimensions: quality, academic culture and competency model. This arises from the problems raised in the Bachelor in Sciences of Communication from the University of Sonora in Mexico with the implementation of the new educational model based on competencies in the author's affiliation place and discipline that distinguishes their training. The methodological process undertaken during the development of this research is contextualized and exposed from a description and reflection of the origin of the problem concerning quality and academic culture in relation to the Competency Based Educational Model. This is analyzed from the perspective of teachers, quality and academic culture of this educational model and the conditions required for the competency model as a new educational project aimed at responding to current needs are outlined.